A study of home telehealth diffusion among US home healthcare agencies using system dynamics. Issue 3 (2nd July 2016) - Kilinc, Mehmet Serdar; Bennett Milburn, Ashlea
ABSTRACT: Home telehealth is a type of telemedicine technology that enables the collection and remote transmission of health data from a patient to a healthcare provider. It enables healthcare professionals to remotely monitor the health progress of patients, especially those with chronic illnesses, on a daily basis. By utilizing home telehealth, home healthcare agencies can provide better chronic care while reducing costs. Furthermore, the use of home telehealth has been shown to decrease the utilization of more acute care services, such as hospitalizations and emergency department visits. Hence, a widespread adoption of HT technologies holds great potential for the current US healthcare system. In this study, a Bass diffusion model is used to understand the diffusion of home telehealth among home healthcare agencies in the US over time. The diffusion model is embedded within a system dynamics model to study how home telehealth will impact the long-term utilization of services in the US healthcare system. The potential benefits of home telehealth over a ten-year horizon are projected in a computational study. Results indicate significant cost savings in even the most conservative test instances studied.